Clinical and Preclinical Evidence for Roles of Soluble Epoxide Hydrolase in Osteoarthritis Knee Pain. Issue 4 (7th March 2022) - Gowler, Peter R. W.; Turnbull, James; Shahtaheri, Mohsen; Gohir, Sameer; Kelly, Tony; McReynolds, Cindy; Yang, Jun; Jha, Rakesh R.; Fernandes, Gwen S.; Zhang, Weiya; Doherty, Michael; Walsh, David A.; et al.
Abstract : Objective: Chronic pain due to osteoarthritis (OA) is a major clinical problem, and existing analgesics often have limited beneficial effects and/or adverse effects, necessitating the development of novel therapies. Epoxyeicosatrienoic acids (EETs) are endogenous antiinflammatory mediators, rapidly metabolized by soluble epoxide hydrolase (EH) to dihydroxyeicosatrienoic acids (DHETs). We undertook this study to assess whether soluble EH–driven metabolism of EETs to DHETs plays a critical role in chronic joint pain associated with OA and provides a new target for treatment. Methods: Potential associations of chronic knee pain with single‐nucleotide polymorphisms (SNPs) in the gene‐encoding soluble EH and with circulating levels of EETs and DHETs were investigated in human subjects. A surgically induced murine model of OA was used to determine the effects of both acute and chronic selective inhibition of soluble EH by N‐[1‐(1‐oxopropy)‐4‐piperidinyl]‐N′‐(trifluoromethoxy)phenyl]‐urea (TPPU) on weight‐bearing asymmetry, hind paw withdrawal thresholds, joint histology, and circulating concentrations of EETs and DHETs. Results: In human subjects with chronic knee pain, 3 pain measures were associated with SNPs of the soluble EH gene EPHX2, and in 2 separate cohorts of subjects, circulating levels of EETs and DHETs were also associated with 3 pain measures. In the murine OA model, systemic administration of TPPU both acutely and chronically reversed established pain behaviors and decreased circulating levels of 8, 9‐DHET and 14, 15‐DHET. EET levels were unchanged by TPPU administration. Conclusion: Our novel findings support a role of soluble EH in OA pain and suggest that inhibition of soluble EH and protection of endogenous EETs from catabolism represents a potential new therapeutic target for OA pain.